2018
DOI: 10.1002/14651858.cd000146.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine replacement therapy versus control for smoking cessation

Abstract: Background Nicotine replacement therapy (NRT) aims to temporarily replace much of the nicotine from cigarettes to reduce motivation to smoke and nicotine withdrawal symptoms, thus easing the transition from cigarette smoking to complete abstinence. Objectives To determine the e ectiveness and safety of nicotine replacement therapy (NRT), including gum, transdermal patch, intranasal spray and inhaled and oral preparations, for achieving long-term smoking cessation, compared to placebo or 'no NRT' interventions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
351
1
34

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 444 publications
(394 citation statements)
references
References 386 publications
8
351
1
34
Order By: Relevance
“…The latter serves as a partial agonist at these receptors, acting as a weak agonist in the absence of nicotine, and as a partial antagonist in the presence of nicotine 17 . While the in vitro receptor binding mechanisms of these drugs and their efficacy at a clinical level is established [18][19][20] , it is less clear how their systemslevel neurobiological mechanisms affect the cognitive and affective deficits seen in the human NWS.…”
Section: Introductionmentioning
confidence: 99%
“…The latter serves as a partial agonist at these receptors, acting as a weak agonist in the absence of nicotine, and as a partial antagonist in the presence of nicotine 17 . While the in vitro receptor binding mechanisms of these drugs and their efficacy at a clinical level is established [18][19][20] , it is less clear how their systemslevel neurobiological mechanisms affect the cognitive and affective deficits seen in the human NWS.…”
Section: Introductionmentioning
confidence: 99%
“…We identified five RCTs of NRT (patches, gum), which is one of the most widely studied pharmacotherapies for smoking cessation [12,13]. We identified five RCTs of NRT (patches, gum), which is one of the most widely studied pharmacotherapies for smoking cessation [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…There are still relatively few RCTs of smoking cessation in LMICs compared to high-income countries. We identified five RCTs of NRT (patches, gum), which is one of the most widely studied pharmacotherapies for smoking cessation [12,13]. A recent systematic review of 136 trials of NRT compared to placebo with a follow-up duration of at least 6 months [13] found an effect size of 1.55 (95% CI = 1.49-1.61), similar to the present analysis (OR = 1.76, 95% CI = 1.30-2.37), suggesting that NRT may have similar efficacy irrespective of the country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations